Role-playing games of Japan: transcultural dynamics and orderings - Kamm, Björn-Ole (Springer International Publishing, 2020)
1. Introduction – Before Play -- 2. Games – Playing with Borders of Reality, or the First Act -- 3. Stereotypes – The Agency of Labels, or the Second Act -- 4. Mediation – Counterpoints of Dis/Connection, or the Third Act -- 5. After Play – Knowledge (and) Practices.
Keywords: Hochschulschrift; Globalisierung; Pen-&-Paper-Rollenspiel; Japan; Rollenspiel